2020
DOI: 10.3168/jds.2019-17556
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis and meta-regression of the effects of vitamin E supplementation on serum enrichment, udder health, milk yield, and reproductive performance of transition cows

Abstract: Vitamin E is an essential nutrient for cows, but the effect of vitamin E supplementation is often controversially discussed in the published literature. The main goal of this meta-analysis was to evaluate the effects of vitamin E supplementation on its serum and colostrum enrichment, milk yield (MY), and somatic cell counts (SCC), as well as on various reproductive variables of transition cows, by considering a large set of variables that might influence the responses to vitamin E supplementation. After a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Extending this research to populations of multiparous dairy cows would be beneficial to the mastitis research community. Additionally, a recently published meta-analysis assessed the effects of vitamin E and vitamin E with selenium adjuvants on SCC in milk (Moghimi-Kandelousi et al, 2020), but future work could include other vitamin and mineral products such as β-carotene and vitamin A. Santos et al (2019) conducted a meta-analysis on the effect of a prepartum DCAD on production performance and health of dairy cattle, by means of altering the mineral composition of diets, and found that less than half of included studies reported the effect of DCAD on mastitis.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Extending this research to populations of multiparous dairy cows would be beneficial to the mastitis research community. Additionally, a recently published meta-analysis assessed the effects of vitamin E and vitamin E with selenium adjuvants on SCC in milk (Moghimi-Kandelousi et al, 2020), but future work could include other vitamin and mineral products such as β-carotene and vitamin A. Santos et al (2019) conducted a meta-analysis on the effect of a prepartum DCAD on production performance and health of dairy cattle, by means of altering the mineral composition of diets, and found that less than half of included studies reported the effect of DCAD on mastitis.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Several other factors affect α-Toc availability and its physiological functions in cows, including the source of the α-Toc active substance, other fat-soluble nutrients in feeds, timing and period of supplementation, inclusion of Se, α-Toc content of the basal feeds, and method of administration (e.g., ruminal pellets or premixes in diet, or iv, sc and im injection). Moghimi-Kandelousi et al [151] evaluated the effects of α-Toc supplementation on the serum level, milk yield, and SCC values of transition cows by considering a large set of variables that might influence the responses to α-Toc supplementation. To conduct a comprehensive meta-analysis of α-Toc supplementation effects during the transition period, after a broad search in journals and databases with keywords related to transition cows supplemented with VE and appropriate filtering of the results, 36 papers including 53 trials were selected from 528 publications (from 1979 to 2018), and their data were extracted into a database.…”
Section: Udder Health (Mastitis and Scc Values) And Milk Yieldmentioning
confidence: 99%
“…Studies have shown that dietary VE can scavenge free radicals, enhance antioxidant capacity and immunity, and improve the performance of cows. The study found that a VE supplementation in diets could reduce the MDA content in cells to a certain extent, improve the antioxidant enzyme activity, enhance the antioxidant capacity in the rumen and body of cows, and reduce the inflammatory response [7]. It found that VE could alleviate the rumen oxidation effect, improve the fermentation yield of cows, and change the availability of rumen energy, thus benefiting the growth of rumen microorganisms [8].…”
Section: Introductionmentioning
confidence: 97%